Predicting Bank Failures: Empirical Evidence from Asian Banks - Abdul Rahim, Raiyan (2010)
This study compares different empirical models to assess the probability of failure of Asian banks; the Probit model and the Cox proportional hazard model. The determining factors are bank-specific but not confined to traditional financial indicators which only assess capital adequacy, asset quality, earnings and liquidity. Our study extends banking performance evaluation by including indicators which capture information relating to the bank’s business structure, off balance sheet items, derivative investments and credit risk. Our study analyzes banking failure in nine countries in Asia over the last decade. We discover that the Probit model and the Cox proportional hazard model produce very similar results in assessing the probability of a bank becoming inactive. All traditional indicators were shown to be influential factors but for the non-traditional indicators, only ratios for derivatives and credit risk were found to be significant.